THE INFLUENCE OF INFORMATION GAP TECHNIQUE IN IMPROVING SPEAKING ABILITY FOR EFL STUDENTS AT FIRST GRADE STUDENTS SMPN 1 RAMBAH HILIR - Neni Triana; Fenny Anita (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
Information gap technique is a technique teaching where students are missing information necessary to complete a task or solve a problem, and must communicate with their classmates to fill in the gaps. The main purpose of this study was to find out the influenced of using Information gap technique for first grade students in SMPN 1 Rambah Hilir in speaking ability. The design of this research was with pre test and post test procedures. The sample was 64 students that divided into two groups, experimental group and control group. The data was analyzed using t-test method to find out whether there were significant differences between experimental group was taught using Information gap technique and control group was not Information gap technique. It found that the students’ speaking ability at SMPN 1 students’ speaking ability at SMPN 1 Rambah Hilir after using information gap had 75.74 with the level of ability good and in control group the average score 59.90 with the level of ability was in mediocre. It means that information gap was effective to use in teaching speaking in order to improve the students’ speaking ability. In other words, information gap was significant in improving the first year students’ ability in speaking at SMPN 1 Rambah  Hilir.